The Influence of Human Resources Competence, Utilization of Digital Tracking, and Road Infrastructure Conditions on Cargo Delivery Timeliness - iIvnu Adam Baihaqi; Muhammad Tohir AMTru, MMTr (Siber Journal of Advanced Multidisciplinary, 2025)
On-time cargo delivery is a key indicator of service quality in the rapidly growing logistics industry. This study aims to analyze the influence of human resource (HR) competency, the use of digital tracking, and road infrastructure conditions on on-time cargo delivery. The method used was a literature review based on a Systematic Literature Review (SLR), examining various scientific literature related to logistics, supply chain management, and digital technology. The study results indicate that HR competency, including technical skills, team coordination, technology adaptation, and workload management, significantly improves on-time delivery. The use of digital tracking allows for real-time monitoring of fleet and cargo status, thus minimizing delays. Good road infrastructure, including surface conditions, capacity, and smooth traffic flow, also directly impacts delivery efficiency. Based on the literature synthesis, these three factors positively influence on on-time cargo delivery. This study formulates a hypothesis for further study: HR competency, digital tracking, and road infrastructure conditions each positively influence on on-time cargo delivery. These findings provide a conceptual basis for more effective operational strategies to improve logistics performance and customer satisfaction.